2009
DOI: 10.1123/japa.17.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Getting Grounded Gracefully©: Effectiveness and Acceptability of Feldenkrais in Improving Balance

Abstract: The Getting Grounded Gracefully© program, based on the Awareness Through Movement lessons of the Feldenkrais method, was designed to improve balance and function in older people. Fifty-five participants (mean age 75, 85% women) were randomized to an intervention (twice-weekly group classes over 8 wk) or a control group (continued with their usual activity) after being assessed at baseline and then reassessed 8 wk later. Significant improvement was identified for the intervention group relative to the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…In conclusion, the present study showed that self-monitoring has in itself some beneficial effects for the improvement of postural stability when maintaining the stability is challenging. This conclusion supports an intuitive understanding of the importance of self-monitoring when performing physical exercises [15][16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 57%
“…In conclusion, the present study showed that self-monitoring has in itself some beneficial effects for the improvement of postural stability when maintaining the stability is challenging. This conclusion supports an intuitive understanding of the importance of self-monitoring when performing physical exercises [15][16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 57%
“…Similarly to the effects of yoga and soft gymnastics, practicing the Feldenkrais Method (Connors et al, 2009;Vrantsidis et al, 2009) and Tai Chi (Xu et al, 2004;Li et al, 2008) has been found to improve postural control in older participants. Both exercises are characterized as sequences of slow movement aimed at the improvement of body awareness.…”
Section: Introductionmentioning
confidence: 94%
“…A typical finding was that such activities were beneficial to counteract the deleterious effect of aging (Gauchard et al, 1999;Connors et al, 2009;Li et al, 2009;Vrantsidis et al, 2009). For instance, Gauchard et al showed that, in comparison to performing bioenergetic physical activities, including jogging, swimming, or cycling, practicing relatively slow physical activities, such as yoga or soft gymnastics, was more effective for older participants to improve their postural control when participants closed their eyes.…”
Section: Introductionmentioning
confidence: 95%
“…Examples of the 10 items assessing indoor activities are getting dressed and bathing; crossing roads and using public transport are examples of the 4 outdoor activities assessed. The mFES has been used in empirical research investigating falls within a community-dwelling elderly population [31], improvements in fall rates in the elderly via training [32], and in analyses of the effect of fear of falling on gait in the elderly [33].…”
Section: Modified Falls Efficacy Scalementioning
confidence: 99%